What kind of joblessness affects crime: a national case-control study of serious property crime - Kleck, Gary (Journal of quantitative criminology, 2016)
Objective To assess whether joblessness affects the commission of serious property crime. Methods We studied serious property crime, applying a case–control design to nationally representative samples of (a) known serious property crime offenders and (b) nonoffenders. This was done by comparing a national sample of prison inmates convicted of robbery or burglary (the “cases”) with a general sample of the U.S. adult population (the “controls”). In contrast to prior individual-level research, the study sample included substantial numbers of serious offenders, and provided a formal basis for generalizing the findings to the U.S. adult population. We differentiated five labor force statuses: (1) unemployed (according to the official government definition), (2) underemployed, (3) out of the labor force for widely socially accepted reasons (OLFL), (4) out of the labor force for reasons not widely accepted (OLFN), and (5) fully employed. Results We found that when these distinctions are made, people are not more likely to engage in burglary or robbery when they are either completely unemployed or underemployed according to the official definitions. Instead, it is being out of the labor force for reasons not widely accepted as legitimate that is significantly and positively related to serious property offending. Conclusions The results suggest that offending among jobless persons may reflect preexisting differences in criminal propensity among those who stay out of the labor force, rather than effects of joblessness per se. Part-time work is associated with significantly less property crime, perhaps because the willingness to accept even part-time jobs serves as an indicator of commitment to pro-social attitudes.